Konsep Layanan Humanistik Dalam Bank Syariah (Tinjauan Nilai-Nilai ESQ Ary Ginanjar Agustian) - Hamidahyati, Hamidahyati; Liliany Purnama Ratu; Novita Sari (El-Ghiroh : Jurnal Studi Keislaman, 2025)
Service in Islamic banking is not only oriented toward compliance with the principles of fiqh muamalah, but also needs to prioritize humanistic values rooted in spirituality. This article aims to examine the concept of humanistic service in Islamic banks using the Emotional Spiritual Quotient (ESQ) approach developed by Ary Ginanjar Agustian. The ESQ approach emphasizes the integration of intellectual (IQ), emotional (EQ), and spiritual (SQ) intelligence as a foundation for building services that are not only efficient, but also meaningful, ethical and spiritual. Through literature study and a descriptive-qualitative approach, this study finds that ESQ values such as honesty, responsibility, compassion, and tawhid-based awareness can strengthen a service ethos oriented toward customer satisfaction and spiritual benefit. Implementing these values in Islamic banking services can enhance customer trust, strengthen loyalty, and shape the institution’s image as one of integrity and Islamic character. This study recommends strengthening ESQ-based training as part of systematic and sustainable human resource development in islamic banking.